The greening of jobs in Germany - Janser, Markus (Nürnberg, 2018)
"The transition towards a greener, less carbon-intensive economy leads to a growing demand for green products, services and business processes. In theory, this trend should lead to a greening of jobs, i.e. to an increasing share of environmentally friendly requirements within occupations (greening of occupations) and to a rising labor demand for employees in these occupations (greening of employment). Due to a lack of measures, there is no empirical evidence on the relationship between the greening of jobs and the real labor market development so far. To fill this gap, the paper measures, describes and analyzes the greening of jobs and its associations with employment and wage growth. The cornerstone of this paper is the new task-based 'greenness-of-jobs index' (goji). The goji is derived by performing text mining algorithms on yearly data from 2006 and 2011 to 2016 of BERUFENET, an occupational data base provided by the German Federal Employment Agency. The descriptive results of the paper show that there is a notable greening of jobs which varies strongly between sectors and regions. The econometric analysis is based on employment register data from 2011 to 2016. The estimation results reveal that the overall level of greenness of occupations is positively correlated with employment growth. Furthermore, the increase of greenness is related to a slight increase in wage growth."